The Development of Swedish Military Healthcare System: Part II—Re-evaluating the Military and Civilian Healthcare Systems in Crises Through a Dialogue and Study Among Practitioners. Issue 3 (26th February 2021) - Khorram-Manesh, Amir; Burkle, Frederick M; Phattharapornjaroen, Phatthranit; Ahmadi Marzaleh, Milad; Sultan, Mohammed Al; Mäntysaari, Matti; Carlström, Eric; Goniewicz, Krzysztof; Santamaria, Emelia; Comandante, John David; Dobson, Robert; Hreckovski, Boris; et al.
ABSTRACT: Introduction: Historical changes have transformed Sweden from being an offensive to a defensive and collaborative nation with national and international engagement, allowing it to finally achieve the ground for the civilian–military collaboration and the concept of a total defense healthcare. At the same time, with the decreasing number of international and interstate conflicts, and the military's involvement in national emergencies and humanitarian disaster relief, both the need and the role of the military healthcare system within the civilian society have been challenged. The recent impact of the COVID-19 in the USA and the necessity of military involvement have led health practitioners to anticipate and re-evaluate conditions that might exceed the civilian capacity of their own countries and the need to have collaboration with the military healthcare. This study investigated both these challenges and views from practitioners regarding the benefits of such collaboration and the manner in which it would be initiated. Material and Method: A primary study was conducted among responsive countries using a questionnaire created using the Nominal Group Technique. Relevant search subjects and keywords were extracted for a systematic review of the literature, according to the PRISMA model. Results: The 14 countries responding to the questionnaire had either a well-developed military healthcare system or units created in collaboration with the civilian healthcare. The results from the questionnaire and the literature review indicated a need for transfer of military medical knowledge and resources in emergencies to the civilian health components, which in return, facilitated training opportunities for the military staff to maintain their skills and competencies. Conclusions: As the world witnesses a rapid change in the etiology of disasters and various crises, neither the military nor the civilian healthcare systems can address or manage the outcomes independently. There is an opportunity for both systems to develop future healthcare in collaboration. Rethinking education and training in war and conflict is indisputable. Collaborative educational initiatives in disaster medicine, public health and complex humanitarian emergencies, international humanitarian law, and the Geneva Convention, along with advanced training in competency-based skill sets, should be included in the undergraduate education of health professionals for the benefit of humanity.